Mutational Profile of Metastatic Breast Cancer Tissue in Patients Treated with Exemestane Plus Everolimus. (24th July 2018) - Omarini, Claudia; Filieri, Maria Elisabetta; Bettelli, Stefania; Manfredini, Samantha; Kaleci, Shaniko; Caprera, Cecilia; Nasso, Cecilia; Barbolini, Monica; Guaitoli, Giorgia; Moscetti, Luca; Maiorana, Antonino; Conte, Pier Franco; et al.
Abstract : Background. Everolimus has been shown to overcome endocrine resistance in hormone receptor positive advanced breast cancer patients. Predictive biomarkers of everolimus efficacy have been investigated in primary breast cancer tissue without finding univocal results. The goal of this study was to investigate the mutational burden in the metastatic site of endocrine-resistant tumors treated with everolimus plus exemestane. Patients and Methods. Mass Array Sequenom platform was used to analyse genetic status of 18 cancer-related genes in 25 archival tumor specimens from metastatic lesions and available primary matched breast cancer tissue of patients treated with everolimus and exemestane for advanced disease. An exploratory analysis of everolimus efficacy in terms of progression free survival benefit and single gene mutation was carried out. Results . The overall detection rate of mutation was 30% and 38% from metastatic and primary breast cancer samples, respectively.A K T 1 E 17 K was the most frequent mutated gene. No primary breast cancer and matched relapse maintained the same mutation profile. Considering molecular pathways, the most of the genes belong to PI3K pathway (A K T 1 E 17 K, P I 3 K C A E 545 K, andK I T G 565 R, S 709 F ). In patients with detected mutations in breast and/or recurrence tissue the median PFS was 5, 6 months while in the subgroup of patients with no mutations the median PFS was 7, 5 months. Conclusions . The mutational status of breast cancer recurrence allows the identification of some genes potentially correlating tumor response/resistance to everolimus. The most frequently mutated genes were involved in the PI3K/AKT/mTOR pathway highlighting that the deregulation of this pathway in the relapse plays a crucial role in the mechanisms of everolimus resistance/sensitivity. Owing to the small sample size and the retrospective nature of the study, these correlations need to be validated in a large prospective study.